Differential Uptake and Utilization of Two Forms of Nitrogen in Japonica Rice Cultivars From North-Eastern China - Yi, Jun; Gao, Jiping; Zhang, Wenzhong; Zhao, Chen; Wang, Yan; Zhen, Xiaoxi (Frontiers in Plant Science, 2019)
Japonica rice is widely planted in north-eastern China because of its superior food quality and stable grain yields. Nitrogen (N) is an essential element for rice growth and development and its availability directly impacts on rice yields. The knowledge of N uptake and its utilization characteristics in japonica are thus important areas of research. Three japonica rice cultivars, SN265, SN1401 and SN9816, which are planted across large areas of north-eastern China, were used here to evaluate the uptake and utilization along the life cycle of both ammonium (NH4+) and nitrate (NO3−) in hydroponically grown plants. The plants were grown in one of three different solutions with varying NH4+ : NO3− ratios: 1:0, 0:1, and 1:1 (The total N content was 40 mg L−1 for each treatment). At the tillering stage, when only NO3− was provided, lower rates of N uptake and enzyme activities of three rice plants resulted in reduced tiller numbers. During the reproductive stage, the NH4+ and NO3− uptake rates in SN1401 were consistently maintained at high levels, whereas the rates in SN265 and SN9816, were significantly lower, across all three treatments. At the booting stage, when only NO3− was provided, SN1401 plants had significantly higher expression levels of OsNRT2.1 and OsNRT2.2, higher activity of nitrate reductase in the roots, and higher activity levels of glutamine synthetase and glutamate synthase in the leaves, compared with the SN265 and SN9816 plants. The higher enzymes activity was beneficial to the secondary assimilation of N, which ultimately promoted panicle development in SN1401. Consequently, the grain yield per plant of SN1401 was the highest with solutions of both NH4+ and NO3−. These results indicate that selecting a rice cultivar with higher utilization of NO3− is beneficial for increasing the number of grains per panicle, grain yield, and N use efficiency.